Transforming Ratus: A Descriptive Qualitative Study on Tradition, Health, and Javanese Women’s Identity - Bambang Haryono; Farida Nurul Rahmawati (Poltekkes Kemenkes Surakarta, 2025)
Background: Ratus as a traditional Javanese health ritual historically associated with purity and marital preparation, has undergone a significant transformation in meaning among contemporary women. This study aims to explore how Ratus is reinterpreted as a cultural, spiritual, and personal practice, revealing women’s bodily agency and negotiation within the dynamics of modernity. Methods: This research employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, nonparticipant observation, and documentation involving eight Javanese women aged 25–50 from Yogyakarta and Bantul, selected purposively for having practiced Ratus for at least two years. Data were analyzed using thematic analysis, supported by source triangulation and member checking to ensure data validity. Results: Five main themes emerged: (1) transformation of Ratus from a sacred ritual to a self-care practice; (2) spiritual and emotional healing dimensions; (3) reinforcement of cultural identity and female solidarity; (4) commodification of tradition within beauty markets; and (5) negotiation between tradition and modernity as symbolic resistance to Western medical and beauty norms. Conclusion: Ratus now functions as both a holistic health practice and a medium of cultural self-expression, reflecting Javanese women’s adaptive agency amid modernization. This study recommends strengthening the preservation of ratus practices through a sustainable cultural approach by involving women, health workers, and community leaders in efforts to maintain its meaning and health benefits.